MIGRASI DAN JARINGAN EKONOMI SUKU BUGIS DI WILAYAH TANAH BUMBU, KERESIDENAN BORNEO BAGIAN SELATAN DAN TIMUR, 1930-1942 - Mansyur Mansyur (Department of History, Faculty of Humanities, Diponegoro University, 2016)
The Bugis migration to Tanah Bumbu, Afdeeling Pasir en de Tanah Boemboe, Residentie Borneo’s Zuid en Oosterafdeeling continued until the early decades of the 20th century, especially in 1930-1942. It was indirectly indicates how strong economic motives of the Bugis. In an effort to survive in the midst of economic depression or malaise, Bugis migrants